Laparoscopic implantation of an artificial urinary sphincter around the prostatic urethra - Chłosta, Piotr (Arab J Urol, 2015)
OBJECTIVE: To report the first laparoscopic periprostatic implantation of an artificial urinary sphincter (AUS) after a transurethral resection of the prostate. BACKGROUND: The implantation of an AUS is a standard procedure for severe urinary incontinence. In men it is usually implanted through a perineal approach, with the cuff placed around the bulbous urethra, bladder neck, or even around the prostate. METHOD: We report a laparoscopic periprostatic implantation of an AUS after a transurethral resection of a prostate in a 72-year-old-man with incontinence. RESULTS: The operative duration was 180 min and the blood loss was 150 mL. There were no complications. After activating the AUS the patient was totally continent. CONCLUSION: The laparoscopic periprostatic implantation of an AUS is a safe, effective and considerably less invasive procedure.